Paediatric clinical teaching: comparison of twomedical schools - Sharma, P.R.; Bhattarai, P.; Sharma, M. (Journal of Institute of Medicine Nepal, 2007)
Clinical paediatric teaching in undergraduate medical education is important to impart essential skills in communicating, diagnosing and formulating management plans for common childhood illness of the country so as to reduce existing high mortality and morbidity rates. Private medical colleges are facing challenges in paediatric teaching because of the unavailability of paediatric patients with different clinical signs; both the inpatient and outpatient paediatric attendance at their teaching hospitals is very discouraging at present. At the same time, they are plagued with inadequate investigative facilities. We conducted a study to evaluate some of the clinical skills in the students during their final examination. The study showed marked differences among students in some of the essential neonatal skills and other common paediatric problems. Statistically significant differences were found in the majority OSCE stations. The mean wrong answers in one medical school were 42.2%(Std D. 30.1%) and the other school was 24.9%(Std.D 18.3%). In one medical school the mean of signs that were rightly performed for the essential neonatal examination were 1.4% (Std. Dev. 1.1 %) and in other schools it was 10.4%(Std. Dev 6.1%). This shows that it is necessary to standardize pediatric teaching in the country’s medical schools. Journal of Institute of Medicine Vol.27(2) 2005